MON-159 High Mortality Rate in Oral Glucocorticoid Users: A Case-Control Study - Einarsdottir, Margret (J Endocr Soc, 2020)
Objective. Long-term oral glucocorticoid (GC) use is associated with increased mortality in patients with rheumatoid arthritis and inflammatory bowel disease. The aim of the study was to investigate whether there is excess mortality among oral GC users, regardless of the underlying disease. Methods. This was a retrospective case-control study. Information on dispensed prescriptions was obtained from the Swedish Prescribed Drug Register. Patients receiving ≥5 mg prednisolone (or equivalent dose of other GC) daily for ≥21 days between 2007-2014 were included. For each patient, a control person, matched for age and sex, was included. The cause of death was obtained from the Swedish Cause-of-Death Registry. Hazard ratio (HR) for mortality was calculated by using Cox proportional hazard model and by the log-rank test. The GC users were divided into four groups according to the length of GC treatment: 1) single-occasion users 2) occasional users (<300 tablets/year); 3) medium-term users (> 300 tablets/year for ≤ 2 consecutive years); and 4) long-term users (>300 tablets/year for > 2 consecutive years). Results. Of 1,585,335 inhabitants in Western Sweden, 223,211 GC users (women 55.6%) were identified for the analysis. The mean age was 48 ± 24 years. Median follow-up time was 3.6 years for GC users and 3.9 years for matched controls. The overall HR for death in oral GC users was 2.26 (95% CI 2.21-2.31). After exclusion of patients with malignant neoplasm, the HR for death was 1.41 (95% CI 1.38-1.45); 1.33 (95% CI 1.27-1.38) in single-occasion GC users (n=112,196), 1.36 (95% CI 1.30-1.42) in occasional users (n=63,862), 1.89 (95% CI 1.79-1.99) in medium-term users (n=19,129) and 1.67 (95% CI 1.51-1.84) in long-term users (n=7,191). The highest HRs were observed for deaths from heart failure (HR 1.71, 95% CI 1.63-1.80), sepsis (HR 1.71, 95% CI 1.51-1.94), and pulmonary embolism (HR 1.87, 95% CI 1.58-2.21). Conclusion. GC users have excess mortality compared to the background population. This illustrates the importance of surveillance for patients on oral GC treatment where adverse effects should be monitored and, when indicated, appropriately treated.